2005
DOI: 10.1038/sj.bmt.1704820
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of pilocarpine hydrochloride for the moderation of oral mucositis during autologous blood stem cell transplantation

Abstract: Summary:Pilocarpine hydrochloride has been reported to increase salivation and decrease oral mucositis in patients receiving head and neck radiotherapy, but there is only one report of its use in a cancer chemotherapy patient population. This prospective, double-blinded, randomized, placebo-controlled trial was undertaken to determine the efficacy of pilocarpine for the moderation of oral mucositis during autologous blood stem cell transplantation. Subjects were randomized to receive a 5 mg tablet of pilocarpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 68 publications
0
9
0
1
Order By: Relevance
“…or combination chemotherapy (ifosfamide, carboplatin and etoposide) plus autologous HSCT (Oblon et al , 1997). Pilocarpine has also been suggested to reduce mucositis (Awidi et al , 2001) but a prospective, double‐blinded, randomized, placebo‐controlled trial in oral mucositis during autologous HSCT showed no benefit (Lockhart et al , 2005).…”
Section: Prophylaxis Of Mucositismentioning
confidence: 99%
“…or combination chemotherapy (ifosfamide, carboplatin and etoposide) plus autologous HSCT (Oblon et al , 1997). Pilocarpine has also been suggested to reduce mucositis (Awidi et al , 2001) but a prospective, double‐blinded, randomized, placebo‐controlled trial in oral mucositis during autologous HSCT showed no benefit (Lockhart et al , 2005).…”
Section: Prophylaxis Of Mucositismentioning
confidence: 99%
“…Saliva plays a major role in oral homeostasis, notably through salivary immunoglobulin A (Epstein et al 2002); however, surprisingly, an attempt to increase production by pilocarpine hydrochloride in cases of decreased or absent saliva (ie, xerostomia) failed to moderate oral mucositis (Lockhart et al 2005). …”
Section: Message Generationmentioning
confidence: 99%
“…66 The topical application of chlorhexidine, 67 GM-CSF, 67 the salivary production stimulator pilocarpine, 68 and histamine gel 69 is not recommended for the prophylaxis of OM given the reported lack of efficacyof these agents. Moreover, no benefits have been found from the use of the amino acid glutamine in the setting of SCT.…”
mentioning
confidence: 99%